ANALISIS DETERMINAN KEJADIAN HIPERTENSI PADA PETANI KOPI DI WILAYAH KERJA PUSKESMAS SIMPANG TIGA KECAMATAN BUKIT KABUPATEN BENER MERIAH TAHUN 2017 - Iriyanti, Maulina; Siregar, Fazidah Aguslina; Aulia, Destanul (Jurnal Farmasindo: Jurnal Penelitian dan Pengabdian Masyarakat, 2020)
Hypertension is a condition in which one ’s blood pressure is above normal rate. Among 972 million people suffering from hypertension, 333 million of them are distributed in developed countries and the other 639 million people are in developing countries, including in Indonesia. The prevalence of hypertension in 2016 reached up to 30%. The objective of the research was to analyze the determinants of hypertension prevalence in coffee growers in the area of Sp. 3 Bukit Sub-district, Bener Meriah District. It is an observational research using case control design. The case group consisted of 55 coffee growers suffering from hypertension and the control group consisted of 55 coffee growers who did not suffer from hypertension, or they were in ratio 1:1. The data were analyzed by multiple logistic regression testing. The variable with the most dominant influence on the prevalence of hypertension in the working are of Puskesmas (Public Health Center) at Sp.3 Bukit Sub-district, Bener Meriah District in 2017 was the habit of drinking coffee with (B) 8.174, 95% CI=3.253 20, 539, p=(0.000) which indicates that patients with hypertension had 8.065 times higher risks to get hypertension attack with frequent coffee drinking habit compared to those who did not suffer from hypertension. It is suggested that medical workers improve health promotion to the society concerning hypertension and provide counseling about the hazard of smoking and drinking coffee resulting in hypertension.